SAT0309 CLINICAL, IMAGING AND BIOLOGIC FEATURES OF SPONDYLOARTHRITIS IN AN AT-RISK POPULATION: DATA FROM THE PRE-SPA COHORT. (June 2019) - Jong, Henriëtte de; Winter, Janneke de; Horst-Bruinsma, Irene van der; Schaardenburg, Dirkjan van; van Gaalen, Floris A.; Tubergen, Astrid van; Weel, Angelique; Landewé, Robert B.M.; Baeten, Dominique; Sande, Marleen van de
Abstract : Background: Diagnosis in axial spondyloarthritis (axSpA) is challenging and often delayed by several years, resulting in a delay in treatment. Previously we reported presence of spondyloarthritis (SpA) features and imaging abnormalities in first-degree relatives (FDRs) of HLA-B27 axSpA patients, who are at risk of developing axSpA [1]. Follow up of these at risk individuals could help to identify clinical signs, imaging abnormalities or biomarkers that are predictive of development of axSpA. Objectives: To investigate imaging, biologic and/or clinical signs of SpA at baseline and after 1 year follow up, as well as development of clinicallly manifest axSpA after 1 year follow up in at risk individuals. Methods: The Pre-SpA cohort[1] is a prospective inception cohort in which FDRs of HLA-B27 positive axSpA patients are included and followed for 5 years. The main exclusion criteria were: a diagnosis of SpA at baseline and back pain with a previous non-rheumatic diagnosis, such as spinal disc herniation. Clinical and biologic characteristics were collected at baseline and after 1 year. Imaging was performed at baseline including MRI of the sacroiliac joints (SIJ) and X-rays of the cervical and lumbar spine and SIJ. MRIs were scored according to the ASAS definition for a positive MRI by two readers. X-rays were scored according to the modified New York (mNY) criteria for ankylosing spondylitis by two readers. Results: In the current study we report the characteristics of 201 participants at baseline and 123 participants after one year of follow-up. 126(62.7%) participants reported back pain, of which 39(19.4%) fulfilled criteria for inflammatory back pain. Median [IQR] VAS total back pain (0-100mm) was 11 (0-28). Six (2.9%) were previously diagnosed with arthritis by a physician, nine(4.4%) with enthesitis and one(0.5%) with dactylitis. In none of these participants a diagnosis of SpA was made. Seven participants were previously diagnosed with an extra-articular manifestation possibly related to SpA: four with psoriasis and three with anterior uveitis. Three (1.5%) participants fulfilled the mNY criteria for sacroiliitis on radiography. Ten (5%) participants had bone marrow edema on MRI of the SIJ suggestive of SpA. Fifty-six (27.8%) participants would have fulfilled ASAS classification criteria for axSpA if they would have had a clinical diagnosis of axSpA. After one year patient-reported disease activity variables remained stable; median [IQR] VAS total back pain (0-100mm) was still low: 4[0-24]. During one year of follow-up, in total seven participants developed symptoms and were clinically diagnosed with axSpA. Conclusion: Imaging signs and clinical signs of SpA are present in a substantial proportion of seemingly healthy FDRs of HLA-B27 positive AxSpA patients. Twelve (6.0%) participants had imaging suggestive of SpA, but a clinical diagnosis of axSpA was still rare after one year of follow up (5.7%). Future follow-up will increase numbers of individuals diagnosed with axSpA and help us identify early symptoms and signs of SpA in this at risk population. Reference: [1] Turina MC, et al., Arthritis Rheumatol. 2016Oct;68(10):2444-55 Acknowledgement: The Pre-SpA cohort is supported by a Dutch Arthritis Society grant Disclosure of Interests: Henriëtte de Jong: None declared, Janneke de Winter: None declared, Irene van der Horst-Bruinsma Grant/research support from: MSD, Pfizer, AbbVie, Consultant for: Abbvie, UCB, MSD, Novartis, Speakers bureau: BMS, AbbVie, Pfizer, MSD, Dirkjan van Schaardenburg: None declared, Floris A. van Gaalen: None declared, Astrid van Tubergen: None declared, Angelique Weel: None declared, Robert B.M. Landewé: None declared, Dominique Baeten Employee of: UCB Pharma, Marleen van de Sande Grant/research support from: Research support from Janssen, Novartis, Eli Lily, Consultant for: Received consultation fees from Abbvie and Novartis